МОДЕЛЮВАННЯ ВИМІРЮВАЛЬНОЇ ІНФОРМАЦІЇ ВИДУ RECEIVED SIGNAL STRENGTH ПАСИВНИХ RFID-МІТОК - Савочкін, Дмитро Олександрович (Збірник матеріалів Міжнародної науково-технічної конференції «ПЕРСПЕКТИВИ ТЕЛЕКОМУНІКАЦІЙ», 2017)
Modeling received signal strength measurement data for passive RFID tags An approach for modeling measurement data of received signal strength (RSS) type for passive RFID tags is presented. The approach takes into account radiation patterns of reader and tags’ antennas and the polarization mismatch.